Assessment of masonry arch bridges by mechanism method - Özer, Onur. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2006., 2006)
There exists several arch assessment methods in the literature which predict theultimate load carrying capacities of masonry arch bridges. The present study elaboratesspecifically on the Mechanism Method.In the first part of this thesis, an algorithm and corresponding computer program has been developed to predict the collapse load of masonry arch bridges. The collapsemechanism is based on the formation of four plastic hinges throughout the structure. Thealgorithm examines all possible sets of such hinge formations and returns the critical one that leads to collapse.The second part of this study concerns a non-dimensional analysis. The aim is toextract a quick estimate for the collapse load of an existing bridge without using any archassessment technique. The proposed method uses the non-dimensional geometric properties of the bridge of interest along with those of tested one(s) for which thegeometric properties and corresponding experimental collapse load are available. Themethod is validated by means of both hypothetical and experimental data.
Keywords: Bridges, Arched.; Bridges -- Design and construction.